Screening and optimization of indole-3-acetic acid production and phosphate solubilization from rhizobacteria aimed at improving plant growth - Chaiharn M. (2014)
A total of 216 bacterial strains were isolated from rice rhizospheric soils in Northern Thailand. The bacterial strains were initially tested for solubilization of inorganic phosphate, indole acetic acid (IAA) production, selected strains were then tested for optimized conditions for IAA production and whether these caused stimulatory effects on bean and maize seedling growth. It was found that all strains had solubilized inorganic phosphate (P), but only 18.05% produced IAA. The best IAA producer was identified by biochemical testing and 16S rDNA sequence analysis as Klebsiella SN 1.1. In addition to being the best IAA producer, this strain was a high P-solubilizer and produced the highest amount of IAA (291.97 ± 0.19 ppm) in culture media supplemented with l-tryptophan. The maximum production of IAA was achieved after 9 days of incubation. The culture requirements were optimized for maximum IAA production. The tested of IAA production by selected isolates was studied in a medium with 0, 0.1, 0.2, 0.5, 0.7, and 0.9% (v/v) l-tryptophan. Low levels (12.6 ppm) of IAA production was recorded without tryptophan addition. Production of IAA in Klebsiella SN 1.1 increased with an increase to 0.2% (v/v) tryptophan concentration. The production of IAA was further confirmed by extraction of crude IAA from this isolate and subsequent Thin Layer Chromatography (TLC) analysis. A specific spot from the extracted IAA production was found to correspond with a standard spot of IAA with the same R f value. The Klebsiella strain SN 1.1 also demonstrated stimulatory effects on bean seedlings in vivo. © 2010 Springer Science+Business Media, LLC.